Penerapan teknologi investment casting pada pembuatan kerajinan perak - Antara, I Nyoman Gde; Jujur, I Nyoman (Jurnal Energi Dan Manufaktur, 2012)
Technology of investment casting has been successfully introduced and applied to the process in producing rings of silver jewelry in cooperative members of silver craftsmen association in Desa Celuk Sukawati Gianyar Bali. In this experiment, the casting equipments used were a principal modified casting machine to avoid a costly production. It was found that the application of investment casting was very prospective method. At once process of the application that took less than a working day, 17 pieces of ring could be produced, where 9 pieces (53%) were excellent and 8 pieces (47%) were invalid. This success is believed can be improved effectively either by controlling or optimizing the working parameters of each equipments in advance. Therefore, the application of the investment casting in producing silver jewelry will assist craftsmen not only to increase their products quality and quantity, but it also will prevent a high production cost compared to those of producing traditionally.
Keywords: Investment casting technology, rings of silver jewelry Korespondensi: Tel./